Estimation of Radiation Dose and Image Quality in Pediatric and Young Adult Computed Tomography Studies - Niiniviita, Hannele (fi=Turun yliopisto|en=University of Turku|, 2017)
Computed tomography (CT) is currently the most important contributor to medical radiation exposure, and pediatric and young adult CT studies raise special concern. A young age and high cumulative effective doses due to repeated CT during follow-up increase the risk of detrimental effects of radiation. Thus, the radiation dose, image quality, and the effects of parameter changes to these two need to be estimated to optimize CT examinations. Thesis examines radiation doses as expressed by computed tomography dose index (CTDI), organ doses and effective doses among pediatric, adolescent and young adult patients. The influence of the CT scanner, patient size, and intravenous contrast agent were studied with regard to the radiation dose and image quality, and the effects of protocol parameter changes were studied to establish a more effective imaging protocol for the assessment of acute appendicitis. Radiation doses were evaluated by phantom measurements using dose monitoring software and dose calculation software. The image quality was evaluated by measuring the contrast to noise ratio and by visual assessment by radiologists. A wide deviation of CT doses was found, despite homogenous cohorts and similar imaging indications. The deviation resulted from differences in the CT devices and non-optimized protocols. High effective doses cumulated during the follow-up of patients with testicular cancer. In the assessment of acute appendicitis, the radiation dose may be reduced, without decreasing image quality, by appropriate protocol adjustments. The large variations in radiation doses and the high cumulative effective doses emphasize the need for setting parameters carefully and for harmonized practices. There is also a need for improved dose monitoring, which may uncover non-optimized protocols.

Säteilyannoksen ja kuvan laadun arviointi lasten ja nuorten aikuisten tietokonetomografia tutkimuksissa Tietokonetomografia (TT) aiheuttaa nykyisin säteilyn lääketieteellisessä käytössä suurimman osan altistuksesta. Lasten ja nuorten TT-tutkimukset sekä seurannasta johtuvat toistuvat TT-tutkimukset ovat nousseet huolen aiheeksi, koska nuori ikä ja korkea kumulatiivinen efektiivinen annos ovat yhteydessä säteilyn haitallisiin vaikutuksiin. TT-tutkimusten optimoimiseksi säteilyannoksen suuruutta, kuvan laatua ja kuvausparametrien vaikutusta näihin pitää pystyä arvioimaan. Tässä tutkimuksessa arvioitiin vastasyntyneen keuhkojen, lasten ja nuorten aikuisten pään ja kaularangan sekä kivessyövän seurannan aikana tehtyjen TT-tutkimusten säteilyannoksia. Käytettävän TT-laitteen, potilaan koon ja varjoaineen vaikutusta säteilyannokseen arvioitiin ja kuvausparametrien vaikutusta kuvan laatuun ja säteilyannokseen arvioitiin tehokkaamman protokollan löytämiseksi akuuttiin appendisiittiin. Säteilyannoksia arvioitiin fantomimittauksilla sekä annosseuranta- ja laskentaohjelmalla. Kuvan laatua arvioitiin mittaamalla kontrasti-kohina suhdetta sekä visuaalisella arviolla. Tutkimuksessa paljastui suurta vaihtelua säteilyannoksissa huolimatta yhtenäisestä kohotista ja indikaatiosta. Vaihtelu johtui erilaisista laitteista sekä epäoptimaalisista protokollista. Lisäksi havaittiin korkeita kumulatiivisia annoksia kivessyövän seurannassa. Akuutin appendisiitin tutkimisessa säteilyannosta voidaan alentaa kuvan laadun kärsimättä sopivalla parametrien muutoksella. Annosten suuri vaihtelu ja korkeat kumulatiiviset annokset osoittavat tarvetta protokollien säätämiselle sekä yhtenäistämiselle. Myös annoksien seurannalle on tarve, jotta mahdolliset epäoptimaaliset kuvausprotokollat saadaan havaittua ja korjattua.